Comparative effectiveness of Dimethyl Sulphoxide (DMSO) and Glycerol as cryoprotective agent in preserving Vero cells (Bangladesh Veterinarian, 2016)
Vero cells have been derived from the kidney of African green monkeys (Cercopithecus aethiops) as mammalian continuous cell lines for biological research. Continuous culturing of Vero cells as well as maintenance of frozen stock is important for future use. Dimethyl sulphoxide (DMSO) and glycerol are two common cryoprotectants used widely to maintain frozen cell lines. DMSO, as a cryoprotectant in cryopreservation procedures, is detrimental to cells. A study was carried out to compare the effect of DMSO and glycerol as cryoprotectants on Vero cells. Vero cells were cultured and maintained using same nutrients and environment, following the modified protocol of Ammerman et al. (2008). After total cell counting the Vero cells were preserved in Cryocane at liquid nitrogen temperature (-196ºC). Two frozen stocks were made simultaneously from the cell suspensions of same concentrations using DMSO and glycerol. After one year of preservation post-thawed cell viability with glycerol was higher than with DMSO. Solutions of 10% glycerol could be the best choice as cryoprotectant for long-term (1 year) preservation of Vero cellsBangl. vet. 2015. Vol. 32, No. 2, 35-41